Ability to Re Create Anecdotal Texts with Structure and Language Attention Students of Class X SMA Negeri 6 Mataram - Adiprasetio Prabowo; David (PT FORMOSA CENDEKIA GLOBAL, 2022)
Based on obtained reality researcher during do observation beginning on during the learning process Indonesian at SMA Negeri 6 Mataram is ability student in create return text anecdote still low. That thing seen when the teacher tells student make text anecdote , student not enough understand method compile or produce text anecdote with good and right. The research design used in this research is quantitative research. The population in this study were all students of class X SMA Negeri 6 Mataram totaling 376 students. Sample is a class X student odd semester SMA Negeri 6 Mataram for the academic year totaling 31 people. Method data collection is observation, task and documentation. The data analysis method in this study is a quantitative descriptive method. The results of this study found that the ability to recreate anecdotal texts by paying attention to structure and language was classified as cumulative performance index (IPK) 70 on normal category. This thing caused because part big student capable explain the structure of anecdotal text, explain language anecdotal text, and write return text anecdote with pay attention structure and his language.